Synthesis and Characterization of Graphene/ITO Nanoparticle Hybrid Transparent Conducting Electrode - Hemasiri, Bastian Waduge Naveen Harindu; Kim, Jae-Kwan; Lee, Ji-Myon (Nano-Micro Letters, 2017)
The combination of graphene with conductive nanoparticles, forming graphene–nanoparticle hybrid materials, offers a number of excellent properties for advanced engineering applications. A novel and simple method was developed to deposit 10 wt% tin-doped indium tin oxide (ITO) nanoparticles on graphene. The method involved a combination of a solution-based environmentally friendly electroless deposition approach and subsequent vacuum annealing. A stable organic-free solution of ITO was prepared from economical salts of In(NO3) ·3 H2O and SnCl4. The obtained ITO nanostructure exhibited a unique architecture, with uniformly dispersed 25–35 nm size ITO nanoparticles, containing only the crystallized In2O3 phase. The synthesized ITO nanoparticles–graphene hybrid exhibited very good and reproducible optical transparency in the visible range (more than 85%) and a 28.2% improvement in electrical conductivity relative to graphene synthesized by chemical vapor deposition. It was observed that the ITO nanoparticles affect the position of the Raman signal of graphene, in which the D, G, and 2D peaks were redshifted by 5.65, 5.69, and 9.74 cm−1, respectively, and the annealing conditions had no significant effect on the Raman signatures of graphene. Highlights: 1 A green, simple, and novel approach was used for hybridization of chemical vapor deposition (CVD) graphene with 10 wt% tin-doped ITO nanoparticles. 2 A unique architecture with monodisperse 23–35 nm ITO nanoparticles over graphene was constructed to form a stable organic-free solution of ITO. 3 High improvements on optoelectrical properties with 28.2% in electrical conductivity relative to individual CVD graphene and more than 85% optical transmittance in the visible range were achieved.